Answer:
Deduction in the step-by-step explanation
Explanation:
If a P0=50.000 deposit is compound every instant, the ammount in the account can be modeled as:
![P(t) = P_(0)*e^(it)](https://img.qammunity.org/2020/formulas/mathematics/college/gig6bq8vzmwdrpl8szud80xokupifu1sjt.png)
If you pull out d dollars a year, the equation becomes:
![P(t) = P_(0)*e^(it)-d*t](https://img.qammunity.org/2020/formulas/mathematics/college/wiwdtjqomb44tgax9rx9ez18a89nh2m80k.png)
If we derive this equation in terms of t, we have
![P(t) = P_(0)*e^(it)-d*t\\dP/dt=d(P_(0)*e^(it))/dt-d(d*t)/dt\\dP/dt=i*P_(0)*e^(it)-d\\](https://img.qammunity.org/2020/formulas/mathematics/college/3y33kydrptw9fek0rt42q3h0a86aihksdi.png)
The first term can be transformed like this:
![i*P_(0)*e^(it) = i*P(t)](https://img.qammunity.org/2020/formulas/mathematics/college/i5be6h1uorvtlfw7448todlc54bbqe0r92.png)
So replacing in the differential equation, we have
![dP/dt=i*P_(0)*e^(it)-d\\dP/dt=i*P(t)-d](https://img.qammunity.org/2020/formulas/mathematics/college/nc7n185ermtnr5yytcgmryj4ncdgi7sl7o.png)
Rearranging
![dP/dt-i*P(t)=-d](https://img.qammunity.org/2020/formulas/mathematics/college/zqf04lk8i7w8rzwysd28k1g9xvzwb9dndh.png)